Sistema RFID de leitura para compras em supermercados - Santos, Gabriel Guilherme Hauagge (2023)
This work aims to present an automated billing system for supermarkets using Radio Frequency Identification (RFID) technology. The proposed system can identify products without the need for barcode scanning, making the shopping experience more efficient and convenient for consumers. It employs a RFID reader equipped with a single antenna to capture information from RFID tags. The antenna has a maximum range of 2 meters, allowing products to be read as they pass within its coverage area. The data collected by the reader is sent to the server, which retrieves the information from a database and forwards it to the user interface system, calculating the total purchase amount. This system offers several advantages compared to traditional billing methods. It is more efficient and practical, reducing waiting times at the checkout line, increasing customer satisfaction, and helping prevent fraud and product counting errors.